Do Civil Servants’ Perceptions of the Implementation of a Merit System Influence the Personal Growth Initiative? - Putra, Anhar Dana; Mannayong, Jumalia (KnE Social Sciences, 2022)
This study aimed to examine the influence of civil servants’ perceptions about the implementation of a merit system on this personal growth initiative of the Regional Civil Service Agency of South Sulawesi province. The data were obtained using two questionnaires, namely the personal growth initiative scale and the perception scale. The research used quantitative methods and linear regression. The results of the study indicated that the perceptions of the merit system implementation had a significant influence on the personal growth initiative of the Regional Civil Service Agency employees. It was found that the magnitude of the effect of perceptions about the merit system implementation on the personal growth initiative was 0.341. Keywords: personal growth initiative, merit system, civil servants